Rethinking relationships - Duck, Steve (Sage, 2011)
"In this book, Steve Duck, a founder of and prolific crossdisciplinary contributor to the field of relationships research, challenges students to re-examine their assumptions about relationships. Duck shows that in order to understand relationships properly, students must understand the roles that society, language, our taken-for-granted assumptions, and other people who share those assumptions play in the conduct of relationships."-Provided by publisher.